Implementation of Good Governance Principles of Sharia Business in Optimizing the Sharia Finance Industry in Indonesia - Suprima (State of Islamic Institute Langsa, 2022)
One important aspect that can encourage the optimization of the Islamic finance industry in Indonesia is good corporate governance (Good Corporate Governance). The reality on the ground, in the sharia financial sector, cases of law violations are still found. As an effort to encourage the implementation of Good Corporate Governance which is intended for sharia business managers in Indonesia, the KNKG issued guidelines for Good Governance for Sharia Business (GGBS). In this study, the authors used a descriptive qualitative approach to the literature study method. The samples or objects that are the source of data in this study are Islamic Commercial Banks (BUS) in Indonesia which publish annual reports for the 2020 period. The results of the analysis of disclosure and assessment using the self-assessment system show that 2 BUS have earned the title very good, 8 BUS received a good predicate, and 3 BUS received a pretty good predicate. However, even though in general the results of the GCG self-assessment were in the good category, violations of the law were still found. Thus, the implementation of GCG in accordance with the GGBS guidelines must be continuously improved, especially in efforts to optimize the Islamic finance industry in Indonesia